Kepribadian dan Etos Kerja Berpengaruh terhadap Produktivitas Kepala Sekolah SD di Kecamatan Pasar Rebo Jakarta Timur - Suryo Wirawan (Jurnal Ilmu Pendidikan (JIP) STKIP Kusuma Negara, 2017)
The objective of this research was to determine the Effect of Personality and Work Ethic to the Productivity of Principal at Junior High School in Pasar Rebo East Jakarta. The research was conducted by using a survey method with path analysis applied in testing hypothesis. The target population size of this research is 68 of principals. Research samples selected as much as 58 principals using simple random sampling technique. Based on this research of data obtained the following conclusions: (1) the personality have positive direct effect to productivity, (2) the work ethic have positive direct effect to productivity, (3) the personality have positive direct effect to work ethic